2019
DOI: 10.1371/journal.pone.0208229
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between growth and wool quality traits of genetically divergent Australian lambs in response to canola or flaxseed oil supplementation

Abstract: The correlations between growth and wool traits in response to canola and flaxseed oil supplementation were evaluated in Australian prime lambs. Sixty dual-purpose prime lambs including purebred Merino and crossbred lambs were allocated to one of five treatments of lucerne hay basal diet supplemented with isocaloric and isonitrogenous wheat-based pellets. Treatments were: no oil inclusion (Control); 2.5% canola oil; 5% canola oil; 2.5% flaxseed oil and 5% flaxseed oil, with lamb groups balanced by breed and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…A prospective cohort study of men in the USA [45] and a cross-sectional survey of Korean adults [46] both reinforced the need to enhance a healthier composition of red meat among consumers to minimize the dietary risks of coronary heart disease, cardiometabolic, and cancer mortality burdens. Previous studies [22,[47][48][49][50][51] had established…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective cohort study of men in the USA [45] and a cross-sectional survey of Korean adults [46] both reinforced the need to enhance a healthier composition of red meat among consumers to minimize the dietary risks of coronary heart disease, cardiometabolic, and cancer mortality burdens. Previous studies [22,[47][48][49][50][51] had established…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acid composition influences the nutritive value and organoleptic traits of meat including tenderness, flavor, and juiciness [20]. The fatty acid content of meat can be affected by the animal production system [21,22], breed or genotype [23,24], gender [25], age at slaughter [26], liveweight [27], level of fatness [20], type of muscle and feed. In lamb [28], cattle, swine, and poultry [29], it has been suggested that dietary manipulation can be utilized to improve the fatty acid content and nutritional value of meat that more closely meets nutritional guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…BZ is an ancient breed that is raised for wool and meat production. Notablely, BZ has undergone long-term selection and is characterized by excellent wool quality (long, uniform and elastic fiber) and white coats, which was mainly raised to provide wool for producing the Tibetan-style blanket 6 . TST has been introduced to crossbred with local breeds to improve the meat-yield performance in China.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Abdel Aal (2018) reported that the almost central staple point of break and the higher elongation rate may be attributed to the fibre diameter and higher crimps frequency recorded. However, moderate to high correlations between fibre diameter and other wool quality traits were detected (Malau-Aduli et al, 2019).…”
Section: Discussionmentioning
confidence: 97%